Потенциальная полипарадигмальность и гибридность педагогических исследований в условиях культурно-научно-образовательного многообразия - Северин, Сергей Николаевич (International Dialogues on Education Journal, 2016)
The article focuses on the scientific paradigm as an “open” regulatory system, and on factors of paradigmatic transformations in pedagogy in the context of post-non-classical culture and science. The author of the article specifies the essence and factors of the potential multiparadigmatic character of pedagogic studies, the potential multiplicity of methodological foundations in the process of solving specific scientific and pedagogical issues. Attention is drawn to the development of pedagogical strategies, to the convergence of pedagogy with culture and science, and to the “hybrid character” of pedagogic studies.